Active hepatitis C virus infection in bone marrow and peripheral blood mononuclear cells from patients with mixed cryoglobulinaemia. - Gabrielli, A (1994)
The presence of hepatitis C virus (HCV) genomic sequences was checked in plasma, liver, peripheral blood mononuclear cells (PBMC) and bone marrow cells from 11 patients with mixed cryoglobulinaemia positive for anti-HCV antibodies, and from 11 patients with chronic HCV hepatitis without serological evidence of cryoglobulinaemia. HCV RNA sequences were demonstrated by reverse transcription polymerase chain reaction in seven plasma samples, in six PBMC samples, and in seven bone marrow cell samples from the 11 cryoglobulinaemic subjects; otherwise, viral specific nucleic acids were detected in 10 plasma samples, in one PBMC sample, and in two bone marrow cell samples from the 11 patients with chronic hepatitis. The HCV replicative intermediate was evidenced in four of the six PBMC and in five of the seven bone marrow aspirate HCV RNA-positive samples. Analysis of subpopulations isolated from bone marrow and peripheral blood samples showed HCV RNA sequences in mononuclear cells belonging either the CD2+ subset or to the CD19+ subpopulation or to the adherent cells. Finally, we compared the nucleotide sequences of a large portion (-270 to -59) of the HCV 5'-untranslated region from five patients with mixed cryoglobulinaemia and from seven patients with chronic hepatitis without cryoglobulinaemia; the degree of heterogeneity, compared with the prototype HCV sequence, was similar in both groups. These findings from two groups of HCV-infected patients indicate that transient or permanent active HCV infection of bone marrow and PBMC is frequent in anti-HCV-positive patients with mixed cryoglobulinaemia, and suggest that extra-hepatic infection may play a major role in influencing the pathophysiology of this infection as well as the viral persistence.